THE INFORMATION SYSTEM OF THE CANADIAN CENTRE FOR OCCUPATIONAL HEALTH AND SAFETY/LE SYSTEME D’INFORMATION DU CENTRE CANADIEN D’HYGIENE ET DU SECURITE AU TRAVAIL - Abeytunga, P. K.; Spinner, B. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2022)
See PDF